Prediction of a New Phase of CuxS near Stoichiometric Composition - Prashant Khatri; Muhammad N. Huda (International Journal of Photoenergy)
Cu2S is known to be a promising solar absorber material due to its suitable band gap and the abundance of its constituent elements. Cu2S is known to have complex phase structures depending on the concentration of Cu vacancies. Its instability of phases is due to favorable formation of Cu vacancies and the mobility of Cu atoms within the crystal. Understanding its phase structures is of crucial important for its application as solar absorber material. In this paper, we have predicted a new crystal phase of copper sulfide (CuxS) around chemical composition of x=1.98 by utilizing crystal database search and density functional theory. We have shown that this new crystal phase of CuxS is more favorable than low chalcocite structure even at stoichiometric composition of x=2. However, Cu vacancy formation probability was found to be higher in this new phase than the low chalcocite structure.